BASIC PHYSICAL QUALITIES OF CHILDREN IN PRE-SCHOOL EDUCATIONAL ORGANIZATIONS CONSTRUCTED FROM VARIOUS TYPES OF BUILDING MATERIALS - Roza T. Kamilova; Ayparshin S. Atamuratova; Khadicha B. Shoyusupova (Central Asian Journal of Medicine, 2024)
Studies have shown that the physical fitness of children depends on the conditions in which they are raised. Preschoolers raised in preschools built from metal structures demonstrate worse physical fitness results compared to their peers raised in brick buildings. A study of 326 children found that children's running speed and jumping ability varied depending on the type of buildings they were raised in, with children raised in institutions built with steel and reinforced concrete showing the worst results. This indicates that the development of physical qualities in preschool children depends not only on regular physical activity, but also on the learning environment, which necessitates the creation of healthy conditions for the formation of an active lifestyle in future generations.